The effect of reading literacy to mathematics comprehension of elementary school students in Indonesia and Malaysia - Anggit Prabowo; Suparman Suparman; Chong Su Li; Dahlia Janan; Tri Dessy Damayanti (International Journal of Evaluation and Research in Education (IJERE), 2023)
This article aims to measure the effects of reading literacy to mathematical comprehension of fifth grade elementary students both in Indonesia and Malaysia. This article used quasi-experiment with factorial design. Samples included 398 students that consisted of 173 elementary students in Indonesia and 216 elementary students in Malaysia. The data were taken by using three instruments: a test and three questionnaires. A test was used to assess the students’ mathematical comprehension. Meanwhile, the questionnaires were used to measure their reading literacy and motivation to study mathematics. They have been validated by two experts and estimated the reliability coefficient by using the Cronbach Alpha formula. Experts judged the instruments were valid based on the content validity. The reliability coefficient of all of the instruments was more than 0.5 so they were reliable. A descriptive statistical analysis was used to describe the data, while the analysis variant was used to examine the different mathematical comprehension levels of the students based on reading literacy and the motivation to study mathematics. The result showed that there is a difference in mathematical comprehension levels between students that have a high reading literacy level and those with a lower level. Besides that, this study also shows that there is a distinction in mathematical comprehension levels between students which have a higher motivation to study mathematics with students that have less motivation. This study concluded that reading literacy and the motivation to study mathematics have an effect toward mathematical comprehension ability of elementary students.